Quantifying and mapping the burden of human and animal rabies in Iraq. - Mashair Z Ismail; Najlaa K Al-Hamdi; Ali N Al-Amery; Denise A Marston; Lorraine McElhinney; Emma Taylor; Victor Del Rio Vilas; Thani M Dadan; Anthony R Fooks; Daniel L Horton (Public Library of Science (PLoS), 2020)
Rabies was first reported in ancient Iraqi civilizations, yet it remains a poorly quantified and important public health threat in the region. Efforts to control rabies in Iraq including dog population control, and vaccination of livestock and dogs, have increased since 2010. Officially reported data on human rabies, dog bites, and animal rabies cases between 2012 and 2017 are analysed here to assess the effect of existing control efforts, to inform future strategies, and to highlight gaps in surveillance and reporting. The results of molecular characterization of 32 viruses from animal cases from throughout Iraq are presented, to improve the understanding of rabies dynamics in the animal reservoir. Although annual numbers of reported human cases were lower in the period between 2012 and 2017 than prior to 2010, human cases continue. There was a distinct gender and age bias among human cases with nine cases in males for every one female and twice as many cases in children than adults. Spatial clustering analysis and phylogenetic evidence suggests rabies is endemic throughout the country, with no regional variation in risk, but better surveillance and reporting is required to underpin control strategies.